Coding Grammatical Relations in Dhimal - Khatiwada, Karnakhar (Gipan, 2017)
Grammatical relations play a vital role not only in the grammar of simple clauses but also in major syntactic processes in Dhimal. The overt coding properties of grammatical relations include nominal morphology and verb agreement in Dhimal. The nominal morphology as coding property presents a consistent nominative pattern of control in Dhimal. The pronominal verb agreement and number agreement also follow the nominative pattern. The Equi-NP deletion (or the co-referent deletion) in complement clauses displays the nominative control in the language.